Influence of storage conditions on the stability of ozonized vegetable oils (Research, Society and Development, 2024)
Ozonation of polyunsaturated vegetable oils imparts antimicrobial, wound healing, and antioxidant properties, expanding their potential applications in pharmaceutical, cosmetic, and food industries. These oils have been increasingly used as natural alternatives in wound treatments due to the formation of reactive oxygen species, such as peroxides, hydroperoxides, and ozonides, during the ozonation process. This study aimed to evaluate the ozonation levels of six polyunsaturated vegetable oils (sunflower, coconut, copaiba, grape seed, olive, and rosehip), using peroxide value as an indicator. Among these, sunflower oil exhibited the highest peroxide value and was selected for detailed monitoring of the ozonation process, including infrared spectroscopy and peroxide value analyses. To assess the effects of storage, the ozonized oil was stored under three conditions: freezer (-18°C), refrigerator (4°C), and room temperature (25°C), with evaluations every 30 days over 180 days. Results demonstrated that room temperature significantly reduced the peroxide value, compromising oxidative stability, while freezer and refrigerator storage better preserved reactive species, such as peroxides, hydroperoxides, and ozonides, with the freezer offering the highest level of conservation. These storage conditions are essential to maintain the antimicrobial and wound-healing potential of ozonized oils, particularly for therapeutic applications. This study highlights the importance of adequate storage strategies to ensure the efficacy and longevity of ozonized oils, contributing to the development of high-value-added products.